Epistemological beliefs and classroom practices of experienced physics teachers: are they related? - Sengul, Ozden (Frontiers in Education, 2024)
This study aimed to explore experienced physics teachers' domain-general epistemological beliefs and classroom practices. The study context was Turkish public high schools in which students with high science and mathematics background could attend based on their middle school grades and standardized test scores. Thirty experienced physics teachers became volunteers to provide data for the study. The data was collected through interviews and classroom observations. During the analysis, qualitative data was analyzed through constant comparative method. Level and frequency of participants' epistemological beliefs and classroom practices were quantified for descriptive statistics. The results indicated that most teachers held transitional epistemological beliefs, but they taught in traditional ways. Their epistemological beliefs and classroom practices were not in alignment. These results showed that experienced teachers might have sophisticated epistemological beliefs, but they were not able to reflect their beliefs into practice according to their perception of students' expectations.